Gender based differences in lipid profile and other novel atherogenic risk factors in type-2 diabetes mellitus patients - Jaidev, Arpita; Shah, Hitesh; Chaturvedi, Mayank K. (International Journal of Research in Medical Sciences, 2021)
Background: Utilization of lipids and lipoproteins gets altered in diabetes mellitus (DM) leading to atherogenic dyslipidemia. This study evaluates cardiovascular risk profile of diabetic men and women, including conventional lipid profile and novel risk factors namely lipid ratios, atherogenic coefficient and atherogenic index. Methods: In all 200 diabetic patients (100 males and 100 females) aged 18-65 years who were under treatment were randomly sampled for the study. Socio-demographic data were collected. Glycated hemoglobin levels, lipid profile, fasting blood sugar, were estimated using standard procedures. Anthropometric variables such body mass index (BMI) was measured, systolic and diastolic blood pressures were also taken. There was no difference between men and women with respect to duration of DM and type of treatment. Results: Lipid profile estimates showed that diabetic females had higher level of total cholesterol (TC) (198.07 vs 169.5 mg/dl) and higher level of high-density lipoprotein (HDL)-C (43.99 vs. 41 mg/dl) as compared to males. All the parameters that are raised total cholesterol, triglyceride levels and low-density lipoprotein (LDL) levels were observed in significantly higher proportion of females as compared to males. The values of atherogenic indices [CR1, CR2, AC and atherogenic index of plasma (AIP)] for both genders were higher than the baseline value. In this study females had higher mean non-HDL 154 mg/dl as compared to males mean non-HDL 129 mg/dl and this study showed that female participants held on in high-risk AIP category and so they were at a higher risk of developing coronary heart condition. Conclusions: Dyslipidemia was observed in a greater proportion of female diabetic patients than male diabetic patients.